2018
DOI: 10.1371/journal.pone.0203489
|View full text |Cite
|
Sign up to set email alerts
|

Novel coronavirus-like particles targeting cells lining the respiratory tract

Abstract: Virus like particles (VLPs) produced by the expression of viral structural proteins can serve as versatile nanovectors or potential vaccine candidates. In this study we describe for the first time the generation of HCoV-NL63 VLPs using baculovirus system. Major structural proteins of HCoV-NL63 have been expressed in tagged or native form, and their assembly to form VLPs was evaluated. Additionally, a novel procedure for chromatography purification of HCoV-NL63 VLPs was developed. Interestingly, we show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 70 publications
1
39
0
Order By: Relevance
“…Therefore, more work in this area is needed before extra-pulmonary symptoms are definitively linked to severe MERS-CoV. Several studies have also shown downregulation causes severe lung pathologies in CoV models of infection, and impairment in cardiovascular health in general [38,39]. Further, progression to ARDS and subsequent cytokine expansion, including IL-8 and 6, CXCL10, and CCL2, and complications such as pulmonary fibrosis, neovascularization, and congestive heart failure due to bilateral pulmonary infiltrates have been noted for infections [2,40].…”
Section: Mers-cov Pathogenesis and Clinical Manifestationsmentioning
confidence: 99%
“…Therefore, more work in this area is needed before extra-pulmonary symptoms are definitively linked to severe MERS-CoV. Several studies have also shown downregulation causes severe lung pathologies in CoV models of infection, and impairment in cardiovascular health in general [38,39]. Further, progression to ARDS and subsequent cytokine expansion, including IL-8 and 6, CXCL10, and CCL2, and complications such as pulmonary fibrosis, neovascularization, and congestive heart failure due to bilateral pulmonary infiltrates have been noted for infections [2,40].…”
Section: Mers-cov Pathogenesis and Clinical Manifestationsmentioning
confidence: 99%
“…Production and purification of VLPs. HCoV-NL63 VLPs composed of the M, E, N, and (optionally) S proteins were produced in insect cells, as previously described (22), with the modification that the N protein was also included. To evaluate protein expression, insect cells infected with bicistronic recombinant baculovirus (rBV) coding for M and E proteins (MϩE) and monocistronic N rBV (and optionally monocistronic S rBV) were immunostained and examined under a confocal microscope.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the apparent molecular weight of the S protein band was higher than expected, most likely because of the glycosylation and/or incomplete denaturation of the protein trimer. Both VLPs, composed of M, E, and N (MEN) and M, E, N, and S (MENS) proteins, were concentrated and purified using a heparin column according to a previously developed protocol (22) (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations